2020
DOI: 10.1113/jp280318
|View full text |Cite
|
Sign up to set email alerts
|

Long‐duration spaceflight alters estimated intracranial pressure and cerebral blood velocity

Abstract: During long-duration spaceflights, some astronauts develop structural ocular changes including optic disc oedema that resemble signs of intracranial hypertension. r In the present study, intracranial pressure was estimated non-invasively (nICP) using a model-based analysis of cerebral blood velocity and arterial blood pressure waveforms in 11 astronauts before and after long-duration spaceflights. r Our results show that group-averaged estimates of nICP decreased significantly in nine astronauts without optic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…Long‐term alterations in hydrostatic gradients change cerebral perfusion pressure (mean arterial pressure at the brain minus ICP) but relatively constant cerebral blood flow or velocity is achieved by autoregulatory adaptation on changing posture or spaceflight. Iwasaki and colleagues (2021) reported higher post‐flight cerebral blood velocity but this finding deserves further investigation. Ocular blood flow is influenced by ocular perfusion pressure (OPP = MAP at the eye minus IOP), but there is evidence that ocular vascular resistance operates over a more limited autoregulatory range to increases in OPP (Schmidl et al .…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Long‐term alterations in hydrostatic gradients change cerebral perfusion pressure (mean arterial pressure at the brain minus ICP) but relatively constant cerebral blood flow or velocity is achieved by autoregulatory adaptation on changing posture or spaceflight. Iwasaki and colleagues (2021) reported higher post‐flight cerebral blood velocity but this finding deserves further investigation. Ocular blood flow is influenced by ocular perfusion pressure (OPP = MAP at the eye minus IOP), but there is evidence that ocular vascular resistance operates over a more limited autoregulatory range to increases in OPP (Schmidl et al .…”
mentioning
confidence: 92%
“…In this issue of The Journal of Physiology , Dr Iwasaki and colleagues (2021) make an important contribution to understanding the potential aetiology of SANS in their report of pre‐ and post‐spaceflight non‐invasive estimation of intracranial pressure (nICP). nICP was actually lower or unchanged after spaceflight in 10 of 11 astronauts, a finding counter to the assumption of elevated ICP that prompted the initial syndrome name, VIIP.…”
mentioning
confidence: 99%
“…Alterations in cerebral circulation and intracranial pressure (ICP) induced by the cephalad fluid shift during spaceflight may be partially related to health problems in astronauts, such as headache ( 1 ) and space-associated neuro-ocular syndrome (SANS) ( 2 ). To better understand these important health issues in the field of space medicine, various studies focusing on cerebral circulation and ICP have been conducted in recent years ( 3 , 4 ). However, the etiology of SANS remains contentious ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…If anything, cerebral autoregulation was improved after the mission [94]. During more long-term missions, cerebral blood flow velocity increased in proportion to a reduction in hemoglobin levels [95]. The authors suggested that increased flow may have compensated reductions in blood oxygen carrying capacity.…”
Section: Is Cerebral Autoregulation Perturbed After Space Flight?mentioning
confidence: 98%